The Relationship Between Cycling Duration and the Level of Knee Pain Complaints and Function in the Elderly: A Study on Members of the An-Nur Lasem Cycling Club - Wahyuni, Wahyuni; Ath-Thariq , Andhika Fatir (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Cycling is categorized as a sport that is favoured by all people because this sport is very easy and simple. Knee pain is the main complaint that often affects the elderly because of the degenerative phase. In the Lasem City area, Central Java, there is the An-Nur elderly bicycle community, the majority of whose members are elderly and complain of pain in the knee area after cycling, that's why researchers want to do this research. The research was carried out to find out whether there is a relationship between cycling duration and functional and knee pain. Methods: This type of research is quantitative observational with a cross-sectional study design. The total sample in this study was 16 people who met the inclusion and exclusion criteria. The results of statistical tests using Chi-Square obtained a p-value of 1.000 for knee pain and 0.551 for functional. Results: The results obtained from this study are that there is no significant relationship between cycling duration and knee pain and function. Conclusion: There was no significant relationship between the relationship between cycling duration and knee pain and functionality.